Teaching an old dog new tricks: re-engineering IL-2 for immuno-oncology applications - Mario Sznol; Naiyer Rizvi (Journal for ImmunoTherapy of Cancer)
Various approaches are being explored to address the unmet medical need among patients with advanced cancer who do not respond to immune checkpoint inhibitors. Interleukin-2 has become a prominent focus of preclinical and clinical investigation, because of its known clinical activity, the important role of this cytokine in immune biology, and the ability to engineer variant proteins with potentially improved antitumor immunomodulatory activity and reduced toxicity. Bempegaldesleukin, the first of the modified IL-2 agents to reach phase 3 evaluation in combination with an anti-PD-1, did not improve outcome for patients with metastatic melanoma and renal carcinoma. The disappointing data raise important questions about the potential efficacy of other interleukin-2 variants, however, several of the other variants appear to be sufficiently differentiated in anticipated pharmacokinetic properties and immune modulatory effects to warrant continued clinical development.